Working memory filtering continues to develop into late adolescence. (April 2016) - Peverill, Matthew; McLaughlin, Katie A.; Finn, Amy S.; Sheridan, Margaret A.
Highlights: Scant research has examined neural correlates of development of working memory filtering. Working memory filtering was examined in adults and adolescents using fMRI. Age-independent neural recruitment for load and filtering was as expected. Adolescents differed from adults in neural recruitment to load in non-frontal regions. Filter-preparatory activity in the basal ganglia supported filtering in adults only. Abstract: While most measures of working memory (WM) performance have been shown to plateau by mid-adolescence and developmental changes in fronto-parietal regions supporting WM encoding and maintenance have been well characterized, little is known about developmental variation in WM filtering. We investigated the possibility that the neural underpinnings of filtering in WM reach maturity later in life than WM function without filtering. Using a cued WM filtering task (McNab and Klingberg, 2008 ), we investigated neural activity during WM filtering in a sample of 64 adults and adolescents. Regardless of age, increases in WM activity with load were concentrated in the expected fronto-parietal network. For adults, but not adolescents, recruitment of the basal ganglia during presentation of a filtering cue was associated with neural and behavioral indices of successful filtering, suggesting that WM filtering and related basal ganglia function may still be maturing throughout adolescence and into adulthood.